Dystrophic calcification within biologic graft occurring with use of calcium sulfate antibiotic beads masquerading as an enteric fistula. Issue 6 (16th June 2022) - Minor, Samuel; Rowe, Judy; Hoogerboord, Marius
Abstract: The rare (<2%) development of calcium deposits in soft tissue, known as dystrophic calcification (DC) with the use of Stimulan® (Biocomposites Ltd, Wilmington, NC) absorbable, calcium sulfate antibiotic beads (CSABs) in the setting of orthopedic surgery has previously been described. However, the use of CSAB in hernia repair is relatively novel and its association with the development of DC in this setting has not been previously reported. We describe a case where DC following abdominal wall reconstruction with CSAB was misinterpreted on CT imaging as an enteric fistula and almost resulted in an unnecessary emergency surgical procedure.